National identity in relief - Sabhlok, Anu (Elsevier B.V., 2010)
This paper explores disaster relief as a medium, through which national identity manifests, circulates and is produced in local spaces. The objective is to move beyond studies of nationalism that emphasize solely the national scale (or the scale of the state) and to make visible the role of women as productive rather than merely reproductive subjects of national communities. The paper is based on over a year of ethnographic field work conducted between the years 2001-2005, in post-earthquake (2001) and in post-Godhra (2002) Gujarat, India.
Keywords: Disaster relief; Ethnography; Gender